2006
DOI: 10.1016/j.jneuroim.2005.10.006
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of a significant role for CTLA-4 in multiple sclerosis

Abstract: Variation in the cytotoxic T-lymphocyt e -associated protein 4 (CTLA-4) gene plays a significant role in deter mi ning susceptibility to autoi m m u ne thyroid disease and type 1 diabetes. Its role in multiple sclerosis is more controversial. In order to explore this logical candidat e more thoroughly we genotyped 771 multiple sclerosis trio families from the United Kingdom for the 3'untra nslate d region variable num ber tande m repeat, the CT60 single nucleotide polymorp his m (SNP) and five haplotype -taggi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 20 publications
6
18
1
Order By: Relevance
“…However further evidence to support the hypothesis that polymorphism at position 49 of CD152 is associated with susceptibility to MS was not demonstrated. These data are in accordance to the results found in parallel studies by other investigators on predominantly Caucasian samples of ancestry (Bagos et al, 2007;Kantarci et al, 2003;Roxburgh et al, 2006). The range of G allele frequencies in these studies were between 35-56.5 in both HC and MS patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However further evidence to support the hypothesis that polymorphism at position 49 of CD152 is associated with susceptibility to MS was not demonstrated. These data are in accordance to the results found in parallel studies by other investigators on predominantly Caucasian samples of ancestry (Bagos et al, 2007;Kantarci et al, 2003;Roxburgh et al, 2006). The range of G allele frequencies in these studies were between 35-56.5 in both HC and MS patients.…”
Section: Discussionsupporting
confidence: 92%
“…More recent studies in MS patients have not demonstrated sufficient evidence to link a particular genotype of the position 49 dimorphism to MS (Bagos et al, 2007;Roxburgh et al, 2006). However, many of these studies were either small pilot studies or conducted in very homogenous populations such Japan or small Norwegian villages (Fukazawa et al, 1999;Chataway et al, 1998;Kuokkanen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The G 49 allele of CTLA-4 was associated with MS susceptibility in two Scandinavian casecontrol studies (Harbo et al, 1999;Ligers et al, 1999) as well as in Olmsted County (Kantarci et al, 2003), and may influence disease severity in Japanese MS (Fukazawa et al, 1999b). However, multiple other case-control studies found no association with MS susceptibility (Masterman et al, 2000;Rasmussen et al, 2001;Bocko et al, 2003;van Veen et al, 2003a;Bonetti et al, 2004;Teutsch et al, 2004;Fukazawa et al, 2005;Lorentzen et al, 2005;Roxburgh et al, 2006). A family-based study in Canadian MS also found no association (Dyment et al, 2004); however, familybased studies with replication in French and southern European MS found an association, especially in families carrying the HLA-DRB1*15 haplotype (Alizadeh et al, 2003).…”
Section: Cytotoxic T-lymphocyte-associated Protein 4 (Ctla-4 or Cd152)mentioning
confidence: 97%
“…Yet, reports on the association of CTLA-4 with MS have been inconsistent. [32][33][34][35][36][37][38][39][40][41] However confusing the association of CTLA-4 with MS, it is worth considering this gene as a potential contributor to the disease.…”
Section: Ctla-4: a General Marker Of Autoimmunity?mentioning
confidence: 99%